Several Factors Affecting Interest in Investing in the Capital Market - Hamzah Ahmad (Advances in Management & Financial Reporting, 2023)
The purpose of this study was to determine and analyze the effect of investment benefits, investment motivation and education on the interest of student members of the KSPM (Capital Market Study Group) in Makassar to invest in the capital market. The population in this study were KSPM member students at Makassar universities. The sampling technique used was purposive sampling, and 30 respondents were obtained according to the established criteria. This study used primary data obtained by giving questionnaires/statements to all respondents. The analysis technique that will be carried out is data quality test, classical assumption test, multiple linear regression analysis and hypothesis testing. The results showed that partially, the variables of investment benefits, investment motivation and education had a positive and significant effect on the interest in investing in KSPM member students in the capital market. The results of this study are expected to be a supporting reference for investment galleries because investment galleries play a role in providing learning for investors. This research is also expected to provide information to increase student interest in investing.